PROBING-PROMPTING LEARNING IN TEACHING SPEAKING - Rezky Fauziah Fajar (Universitas Muhammadiyah Makassar, 2020)
Based on the result of this study implementation of probing-prompting learning to the ability to speak and curiosity in learning English. That thing is shown by some conclusions as the following: (1) ability to talk about learning model probing-prompting achieve classic equipment; (2) capacity talk to students about models learning probing-prompting better than ability talk to students about models conventional learning; (3) curiosity students on the probing-prompting learning model better rather than a students curiosity about the model conventional learning.